Pediatric Burn Wound Impetigo After Grafting. Issue 2 (March 2015) - Aikins, Kimberly; Prasad, Narayan; Menon, Seema; Harvey, John G.; Holland, Andrew J. A.
<x xml:space="preserve">Abstract</x> Modern burn care techniques have reduced the risk of infection of the acute burn wound, resulting in more rapid healing and a lower incidence of graft loss. Secondary breakdown may still occur. The loss of epithelium in association with multifocal superficial abscesses and ulceration has been termed burns impetigo. This may result in considerable morbidity and require prolonged treatment. The events preceding development, the impact on the patient, and the ideal treatment appear unclear and poorly reported. In 5 years, between 2006 and 2011, 406 pediatric burns were treated with skin grafts, with 7% developing burns impetigo. Time to resolution ranged from 5 to 241 days: the mean time to complete healing was greatest with conservative management (96 days), followed by antibacterial dressings (37 days), oral antibiotics (36 days), topical steroids (16 days), and oral antibiotics in combination with topical steroids (13.5 days). Burns impetigo resulted in significant morbidity, requiring multiple visits to the treatment center and prolonged symptoms. Delay in diagnosis and treatment resulted in worse outcomes. Prompt consideration of burns impetigo should occur when postgraft patients present with suggestive clinical signs and treatment with oral antibiotics plus topical steroids should be considered.